Progressive Islam in Haedar Nashir’s Perspective and Its Implications for Islamic Education in Indonesia - Aljamaedi, Aljamaedi; Yanfaunnas, Yanfaunnas; Syahruddin, Syahruddin; Mursal, Mursal; Lahmi, Ahmad (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This article aims to analyze in depth Haedar Nashir's thoughts on the concept of Progressive Islam and its relevance to strengthening the Muhammadiyah movement and reforming Islamic education in Indonesia. This study uses a qualitative method with a content analysis approach. The research data is sourced from Haedar Nashir's primary works discussing Progressive Islam and Muhammadiyah, as well as secondary sources in the form of scientific journal articles, academic books, previous research results, and official Muhammadiyah documents. Data analysis was conducted using thematic content analysis techniques by classifying the data into main themes, such as the definition of Progressive Islam, its theological and philosophical foundations, basic principles, and its implementation in the Muhammadiyah movement, particularly in the field of education. The results of the study show that Progressive Islam in Haedar Nashir's perspective is a comprehensive and visionary Islamic paradigm, which positions Islam as a moral, intellectual, and social force in building a modern civilization. This concept not only functions as a theological framework, but also as an ideological and strategic foundation for Muhammadiyah in responding to global dynamics, technological disruption, and contemporary humanitarian challenges. In the context of Islamic education, Progressive Islam implies strengthening the integration between religious knowledge and modern science, transforming the orientation of education towards the formation of people who are faithful, knowledgeable, and have superior personalities, as well as developing an adaptive, inclusive, and civilized education system. Thus, Haedar Nashir's thoughts on Progressive Islam contribute significantly to the renewal of Islamic education and the strengthening of Muhammadiyah's role in the development of a just, progressive, and sustainable Indonesian civilization.